A Case of Necrotizing Fasciitis Mimicking a Burn in an Elderly Patient - Madiha Khan; Shubham Bhatia; Kelly L. Cervellione; Martine A. Louis (Case Reports in Surgery)
Necrotizing fasciitis travels along the fascial plane and surrounding soft tissue, leading to ischemia and necrosis. Fournier’s gangrene is a type of necrotizing fasciitis invading the deep and superficial planes of the perineal/genital region. It is rapidly progressive in nature and may have life-threatening consequences. Fournier’s often exhibits a misleading clinical presentation and can be mistaken for other conditions, such as hematoma, phlebitis, cellulitis, or septic arthritis. Since the ramifications of delayed diagnosis can be clinically significant, recognition of potential mimics is important to prevent morbidity or mortality. We report a case of Fournier’s gangrene mimicking a second-degree burn, an exceedingly rare presentation.